Perbandingan Efektifitas Chainsaw Stihl 070 Dan Stihl Ms 381 Pada Kegiatan Penebangan Pohon - Rochmad Hidayat; Wiyono Wiyono; Silvi Nur Oktalina (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Felling is an important aspect in forest management. The effectiveness of felling affects forest management, wood harvesting in particular. For that reason, it is highly needed to understand the effectiveness of using different chainsaws for felling the trees. The purpose of this research is to know the effectiveness and work performance of chainsaw Stihl MS 381 and 070 on felling activities. This research was conducted in KPH Ngawi Perum Perhutani regional division of East Java with Swietenia macrophllya as its forest stand. Then, work time and work result on wood harvesting obtained was taken as research data employing repetitive timing method. Data analysis was conducted by calculating the work result, calculating the volume using Wood Volume Table for mahogany (tabel isi kayu mahoni) and applying T test for testing the significant difference of working performance between Stihl MS 381 and 070. Based on this research, the work performance of chainsaw MS 381 was 1,42 m3/hour or 11,33 m3/day work and for chainsaw 070 was 1,83 m3/hour or 14,63 m3/day work. Both sthil MS 381 and 070 chainsaw performed similar work effectiveness to finish the felling of mahogany stands. It was clearly proved by their work time and work performance which were not much different.